A model of the productive capacity of soils of land cover in Al-Suwayr district using remote sensing technology and geographic information systems - Al Kalidar, Prof. Dr. Quds Osama Qawam (Thi Qar Arts Journal, 2022)
In this research, there is an approach to estimating the quality of soils in an arid environment, as it has an arid and semi-arid climate in southern Iraq, which is Al-Suwayr district of Al-Muthanna Governorate. The technology in the detection of land cover based on the data of the US Geological Survey (earthexplorer.usgs.gov), for the Sentinel satellite and the multispectral satellite (Land sat-OLI TIRS C1) (see attached image 1(a,b,c). ) and working on an analysis of those visuals to monitor and detect land cover changes during several years (2000, 2015, 2021) in terms of changing the area of vegetation, water and urban cover, using the spatial analysis tools in the Spatial Analysis Tool and choosing the Map Algebra- Raster Calculator tool, and that To detect land cover indicators (vegetation index, water index, urban cover index), and soil types will be revealed through the International Union of Soil Sciences working group TSD 2006. Global reference base for soil resources 2 006 from the site (https://soilgrids.org/), see the attachment of the image (2) in order to reach the analysis of soil capacity and its classification in Al-Suwayr district according to the construction of the preferred land cover model according to the analysis of layers (NDWI, NDVI, NDBI), and then Overlay spatial matching and the study concluded that merging the layers of the appropriate land cover model with the layer of soil types and the type of sediment, it was possible to determine the classification of the productive capacity of soil in Al-Suwayr district.